Analisis Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian Di Puskesmas Terara Tahun 2021 - Fitri Haryati (Syntax Corporation Indonesia, 2022)
Patient satisfaction with pharmaceutical services is important for every Puskesmas. Patient satisfaction is a determining factor for good or bad services provided by the Puskesmas. This study aims to determine the description of patient satisfaction with pharmaceutical services at the Terara Health Center. This research is a descriptive research, which is a research method that is carried out to make a description of the objective situation. While the form of implementation of this research is a survey. The survey in question is a public opinion survey. The results showed that the level of patient satisfaction with pharmaceutical services was based on 5 dimensions, namely 1) responsiveness 99%, 2) empathy 99%, 3) reliability 100%), 4) assurance 99%, 5) Tangiable 100%. Thus, it can be concluded that of the five dominant dimensions, which are in the good category, it can be said that the respondent's perception of the level of patient satisfaction with drug services at the Terara Health Center is good.